Effects of quercetin loaded nanostructured lipid carriers on the paraquat-induced toxicity in human lymphocytes - Ahmadian, Elham; Eftekhari, Aziz; Kavetskyy, Taras; Khosroushahi, Ahmad Yari; Turksoy, Vugar Ali; Khalilov, Rovshan (Pesticide biochemistry and physiology, 2020)
Paraquat (PQ) as a herbicide and an environmental pollutant with increasing importance due to its toxicity to humans and animals. This study aimed to evaluate the protective and antioxidant activity of quercetin loaded Nanostructured Lipid Carriers (QNLC) against toxicity induced by PQ. Blood lymphocytes were prepared using Ficoll polysaccharide and subsequently by gradient centrifugation. The QNLC was prepared using an ultra-sonication method, which was characterized by dynamic light scattering (DLS) and transmission electron microscopy (TEM). The viability, reactive oxygen species (ROS), lipid peroxidation (LPO), mitochondrial membrane potential (MMP), lysosome membrane integrity, Bax and Bcl2 gene expression were evaluated in human isolated lymphocytes. The results showed spherical QNLCs with nano-size range (52.7 nm) and high drug encapsulation efficiency (98.5% -96%). The results also indicated that PQ induced cell death, as well as ROS production, decreased by QNLC in human lymphocytes. Also, QNLC meaningfully restored MMP reduction, lysosomal membrane destabilization, and lipid peroxidation and were capable of preventing PQ-treated change in Bax and Bcl2 gene expression. We report that QNLC, have a significantly higher capacity to prevent PQ-induced toxicity than Q itself. It is suggested that the QNLC is a promising antioxidant for drug delivery to be used as a therapeutic and prophylactic agent for PQ poisoning. [Display omitted] •Quercetin loaded NLC protect lymphocytes in paraquat toxicity.•Quercetin loaded NLC mitigate paraquat-medaited oxidative damage.•Paraquat-mediated mitochondrial toxicity reduced by quercetin loaded NLC.